Rigid polyurethane foams made from chemically recycled pet and pcbjpe modelo de artículo - Souza, Kamilly S.; Bigles, Luiz H.; Lima, Luiz H. de; Silva, Paulo da; Silvero, Samuel L.; Passinhas, David Manuel Costa; Melo, Breno Nonato (Brazilian Journal of Production Engineering, 2023)
Polyethylene terephthalate (PET) and polycarbonate (PC) reacted with glycerol produce polyol precursors for polyurethanes. Polyurethanes were synthesized from PET and PC depolymerized in glycerol reacted with 4,4'-diphenylmethane diisocyanate (MDI) in ratios of 0.8 and 1.0 using water as a blowing agent at 0%, 1% and 2%. The hydroxyl content was 287 ± 10 mgKOH/g for the polyol from PET (PET-OL) and 520.99 ± 11.62 mgKOH/g for the polyol from PC (PC-OL). The FTIR spectra of the synthesized PUs showed the typical PU bands (1730 cm-1) and those synthesized from PC-OL showed remnant MDI seen by the band at 2270 cm-1. They had apparent densities of less than 0.6 g/cm3, typical of thermal insulators. The density decreased as the water content increased, as did the NCO/OH ratio. In addition, the materials synthesized with PET-OL are denser than those synthesized with PC-OL. The optical microscopy images of the PU topographies indicate homogeneous materials containing more closed cells than open ones. PU’s made with PC-OL absorb more water than those made with PET-OL.
Keywords: Chemical recycling; Plastics; Polyurethanes